PpCBF6 Is Involved in Phytosulfokine α-Retarded Chilling Injury by Suppressing the Expression of PpLOX5 in Peach Fruit - Jiao, Caifeng (Frontiers in Plant Science, 2022)
The involvement of PpCBF6 in phytosulfokine α (PSKα)-ameliorated chilling injury (CI) by suppressing the expression of lipoxygenase 5 (LOX5) in peach fruit was revealed. The peaches were immersed in distilled water and PSKα solution. PSKα application inhibited the progression of CI index and weight loss, and the reduction of firmness and total soluble solids content in peaches. The endogenous PSKα accumulation and gene expression of PSK receptor 1 (PSKR1) and PSKR2 were up regulated by PSKα application. The superoxide anion (O2–) production rate, hydrogen peroxide (H2O2) production and reactive oxygen species (ROS) content decreased by PSKα application. Furthermore, PSKα application reduced the gene expression of 12 PpLOXs and LOX activity. The gene expression of 6 PpCBFs was enhanced by PSKα application. Importantly, after PSKα application, among 12 PpLOXs, the decrease in gene expression of PpLOX5 was the lowest, and among 6 PpCBFs, the increase in gene expression of PpCBF6 was the highest. Further results suggested that PpCBF6 bound to the C-repeat/dehydration responsive element (CRT/DRE) motif in PpLOX5 promoter, and repressed its transcription. Thus, PpCBF6 was involved in the PSKα-retarded CI by inhibiting the expression of PpLOX5 in peaches.